Effect of catalyst type on molecular weight increase and coloration of poly(ethylene furanoate) biobased polyester during melt polycondensation. Issue 44 (3rd November 2017) - Terzopoulou, Zoe; Karakatsianopoulou, Elisavet; Kasmi, Nejib; Tsanaktsis, Vasileios; Nikolaidis, Nikolaos; Kostoglou, Margaritis; Papageorgiou, George Z.; Lambropoulou, Dimitra A.; Bikiaris, Dimitrios N.
Abstract : The effect of several catalysts on the synthesis of poly(ethylene furanoate) (PEF) was studied during a two-stage melt polycondensation process. Abstract : In this work, the effect of the catalysts tetrabutyl titanate(iv ) (TBT), titanium(iv ) isopropoxide (TIS), tin(ii ) 2-ethylhexanoate (TEH) and dibutyltin(iv ) oxide (DBTO) on the synthesis of poly(ethylene furanoate) (PEF) was studied during a two-stage melt polycondensation process. In all reactions, 2, 5-dimethylfuran-dicarboxylate (DMFD) and ethylene glycol (EG) in 1 : 2 molar ratios, and 400 ppm of catalyst were used. The rate of the transesterification reaction (first stage) was evaluated by measuring the volume of the distilled methanol and for the polycondensation reaction (second stage) by the increase of intrinsic viscosity. For the first stage, all catalysts had a similar effect to methanol distillation, except for TEH which was found to be the slowest catalyst, while for the second stage TIS and TBT were found to be the most effective catalysts, followed by DBTO and TEH, which again had the lowest reactivity. Coloration of the prepared polyesters was measured using the L * a * b * colour space system and was found to be dependent on catalyst type and melt polycondensation time, with titanate catalysts yielding the highest coloration. White coloured polyesters can be obtained after dissolution in trifluroacetic acid and chloroform mixture, and precipitation in methanol. Decomposition by-products formed throughout the different processes were identified in solution and elucidated by using liquid chromatography high resolution mass spectrometry (LC-HRMS). Similar decomposition products were detected in all chromatographs and therefore concentration in samples prepared with titanate catalysts might be the cause of the higher colour intensity of these samples.